THE IMPLEMENTATION OF PANCASILA AS A PHILOSOPHICAL BASIS OF EXERCISING SUFFRAGE - Lulus Udjiwati (Surakarta Law and Society Journal, 2020)
Democratic Party implemented with general elections, citizens frequently unused their suffrage or used their suffrage to get a reward. It is becoming a matter of concern because it results an election which is no longer honest, free, fair and confidential. If every citizen, whether those who are voted or those who vote have an understanding towards the philosophical basis decanted in the values of Pancasila, especially the fourth principle, a popular sovereignty election will be achieved. Pancasila which is a Grundno rm should be the basis for the government to implement the mandate as a representative of the people, while the community can vote the candidates with full consideration, not for any other reasons. Keywords: Pancasila, philosophy, suffrage.